Effectiveness of Stocking Density on Growth and Feed Consumption of Barramundi (Lates calcarifer) - Aulianto, Fikry; Azhar , Fariq; Diniariwisan, Damai (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Barramundi (Lates calcarifer) is a valuable brackish and marine fish species with high aquaculture potential. This research aimed to evaluate the effect of different stocking densities on growth performance and feed efficiency. A completely randomized design (CRD) was used in a uniform floating net cage (FNC) system with four stocking densities: P1 (20 fish/m³), P2 (30 fish/m³), P3 (40 fish/m³), and P4 (50 fish/m³), each with three replications. Results showed that absolute length growth ranged from 1.17 to 2.33 cm, absolute weight growth from 2.36 to 4.43 g, specific growth rate from 0.94 to 1.93%/day, and feed conversion ratio (FCR) from 1.22 to 2.03. The best growth and FCR were observed in P1 (20 fish/m³), while higher densities resulted in reduced performance. The study concludes that lower stocking densities enhance growth and feed efficiency in barramundi aquaculture. These findings provide valuable insights for optimizing stocking strategies to improve productivity and sustainability.